Haemothorax and Thoracic Spine Fractures in the Elderly - Michael A. Masteller; Aakash Chauhan; Harsha Musunuru; Mark M. Walsh; Bryan Boyer; Joseph A. Prahlow (Case Reports in Radiology)
Both osteoporotic fractures and pleural effusions are frequently observed in medicine. However, rarely does one associate a hemorrhagic pleural effusion with a thoracic spinal fracture when the patient has not sustained massive trauma. In this paper, we discuss two cases where seemingly insignificant low-energy trauma precipitated massive haemothoraces in elderly patients with underlying osteoporosis, ultimately resulting in their immediate causes of death. This paper serves to remind health care professionals of the importance of using caution when moving elderly patients as well as to consider thoracic spinal fracture as a potential explanation for a hemorrhagic pleural effusion of undetermined etiology.